Views of communities regarding organ donation in Sekhukhune District of Limpopo, South Africa - Mokabane, Dikeledi Mashego (My University, 2020)
Introduction and background: There is an increase shortage of organs for donation to patients with end stage organ failure worldwide, including in African countries and South Africa as well. Regardless of the number of potential organ donors in South Africa organ availability remain scarce at communities are not actively involved in organ donation. Views of communities regarding organ donation among Sekhukhune communities has not being researched before, the purpose of the study is to explore views of Sekhukhune Community at Limpopo Province of South Africa regarding organ donation. Methodology: Qualitative research method was used, applying descriptive and explorative research designs. The study site was Makhuduthamaga municipality of Sekhukhune district at Limpopo Province, targeting community members as research participants. Fifteen (15) participants were interviewed using semi-structured interviews until data saturation was reached. During data collection the researcher used an interview guide and the participants were audio recorded. Ethical principles were adhered to before and during conduction of the research study. Collected data was analysed using 8 steps of Tech’s coding method. Results: The study revealed that there are different views of community towards organ donation, which contribute to uncertainty, positivity and negativity towards organ donation. Knowledge and understanding of organ donation was found to be a factor that can influence improvement of organ donation among communities at Sekhukhune district. Other factors that were found to contribute the lack of organ donation among communities were religion, culture and stigma attached to organ donation. Conclusion: Community members lack knowledge of organ donation and end up holding in to the myth regarding organ donation. Health awareness, workshop and education to the communities in schools and community facilities such as halls and meetings can improve knowledge on organ donation promoting involvement of community members.
Thesis ( M.A. (Nursing)) -- University of Limpopo, 2020
Keywords: Organ donation; Donation of organs, tissues, etc.